Crystallography of Fe2Al5 phase at the interface between solid Fe and liquid Al. (December 2015) - Takata, Naoki; Nishimoto, Manamu; Kobayashi, Satoru; Takeyama, Masao
Abstract: In this study, the microstructures and crystallographic features of a η-Fe2 Al5 phase formed on pure Fe hot-dipped in a pure Al melt at 750 °C were examined in order to understand the η phase layer formation having a saw-tooth morphology. A number of the columnar η grains (forming the η phase layer) grow towards the solid Fe (α-Fe) side along the [001] direction, resulting in a significant saw-tooth morphology at the interface between the η and α-Fe phases. The neighboring η grains have high-angle boundaries with a common [001] axis. In the η phase layer, the low-angle boundaries develop close to the liquid Al side, and their density becomes higher with longer dipping times, resulting in the development of a fine dislocation substructure in the η phase. In the α-Fe phase, fine substructure consisting of a high density of low-angle boundaries develops around the growth tips of the columnar η grains. These substructure developments are likely responsible for the α → η transformation strain. A possible mechanism for the formation of this η phase layer having a saw-tooth morphology will be discussed in terms of the stress field caused by the α → η transformation. Highlights: Low-angle boundaries within Fe2 Al5 phase develop close to the liquid Al side. The density low-angle boundaries within Fe2 Al5 phase increases at longer times. Fine equiaxed grains with dislocation substructure are within growing Fe2 Al5 phase. The α → η transformation strain/stress might contribute to the saw-tooth morphology.